Effect of APOE and a polygenic risk score on incident dementia and cognitive decline in a healthy older population. Issue 6 (26th May 2021) - Riaz, Moeen; Huq, Aamira; Ryan, Joanne; Orchard, Suzanne G; Tiller, Jane; Lockery, Jessica; Woods, Robyn L.; Wolfe, Rory; Renton, Alan E.; Goate, Alison M.; Sebra, Robert; Schadt, Eric; et al.
Abstract: Few studies have measured the effect of genetic factors on dementia and cognitive decline in healthy older individuals followed prospectively. We studied cumulative incidence of dementia and cognitive decline, stratified by APOE genotypes and polygenic risk score (PRS) tertiles, in 12, 978 participants of the ASPirin in Reducing Events in the Elderly (ASPREE) trial. At enrolment, participants had no history of diagnosed dementia, cardiovascular disease, physical disability or cognitive impairment. Dementia (adjudicated trial endpoint) and cognitive decline, defined as a >1.5 standard deviation decline in test score for either global cognition, episodic memory, language/executive function or psychomotor speed, versus baseline scores. Cumulative incidence for all‐cause dementia and cognitive decline was calculated with mortality as a competing event, stratified by APOE genotypes and tertiles of a PRS based on 23 common non‐ APOE variants. During a median 4.5 years of follow‐up, 324 participants developed dementia, 503 died. Cumulative incidence of dementia to age 85 years was 7.4% in all participants, 12.6% in APOE ε3/ε4 and 26.6% in ε4/ε4. APOE ε4 heterozygosity/homozygosity was associated with a 2.5/6.3‐fold increased dementia risk and 1.4/1.8‐fold cognitive decline risk, versus ε3/ε3 ( p < 0.001 for both). High PRS tertile was associated with a 1.4‐fold dementia risk versus low (CI 1.04–1.76, p = 0.02), but was not associated with cognitive decline (CI 0.96–1.22, p = 0.18). Incidence of dementia among healthy older individuals is low across all genotypes; however, APOE ε4 and high PRS increase relative risk. APOE ε4 is associated with cognitive decline, but PRS is not. Abstract : We studied cumulative incidence of dementia and cognitive decline in 12, 978 healthy older individuals without a history of cardiovascular disease. Dementia incidence was low across all genotype groups, but APOE ε4 and high PRS still increased relative risk. APOE ε4 was associated with cognitive decline risk, but PRS was not.